Synthesis of MnO2 Microfiber with Secondary Nanostructure by Cotton Template - Huan-qin Wang; Ming-bo Zheng; Jin-hua Chen; Guang-bin Ji; Jie-ming Cao (Journal of Nanotechnology)
Hierarchical MnO2 microfibers were prepared by using cotton as the template and KMnO4 as the precursor via an ultrasonic assistance route. The results of scanning electron microscope characterization showed that the concentration of KMnO4 had a significant effect on the morphology of MnO2 microfiber. At low concentration of KMnO4, the microfiber was composed of MnO2 nanorods with single crystal structure. With increasing the concentration of KMnO4, the secondary nanostructure of MnO2 microfibers had a transformation from nanorod to nanoparticle. The results of N2 adsorption-desorption analysis indicated that MnO2 microfibers had BET surface area of about 25 m2/g. This synthesis provides a new way to control the secondary nanostructure of MnO2 microfiber by adjusting the concentration of precursor. Furthermore, the mechanism for the replication was proposed and discussed.